An ageing population and external debt: an empirical investigation - Abd Rahman, Nur Hayati; Ismail, Shafinar; Ridzuan, Abdul Rahim (Journal of Business Economics and Management, 2021)
A rise in the ageing population is the current demographic challenge which is capable of pressuring the government to borrow more external funds in order to support domestic needs. This study aims to investigate the effects of the external debt of 36 upper-middle-income economies from 2000 to 2017 due to the increase in the ageing population. This study employed the system Generalised Method of Moments (GMM), where it revealed that the ageing population could increase the level of external debt if the population aged 65 and above was used as a proxy to represent the ageing population. However, the results were insignificant when the proxy was changed to the old-age dependency ratio. It illustrated that the increase in external debt occurs due to the increase in the population aged 65 and above because the government has to allocate more funds for healthcare, age-friendly infrastructure, social security and pensions. However, the dependency of the older people on government is minimal because of their long-term savings. Hence, the old-age dependency ratio has an insignificant relationship with the external debt level. For future research, it is suggested that the impact of the ageing population can be investigated on the domestic debt level. First published online 23 December 2020